A contribution to the characterization of the silicate-water interface – Part II: Atom Probe Tomography of tricalcium silicate. (November 2018) - Naber, C.; Sowoidnich, T.; Bellmann, F.; Neubauer, J.; DeRocher, K.A.; Joester, D.
Highlights: Nanoscale investigation of two tricalcium silicate polymorphs. APT of tricalcium silicate possible by carefully controlling measurement parameters. Conventional specimen preparation technique harmful to hydrate phases. Abstract: This work explores the possibility to investigate the nanoscale cement-water interface by means of atom-probe tomography (APT). For this purpose, the main compound of Ordinary Portland Cement, tricalcium silicate, and its hydration product calcium-silicate-hydrate have been analyzed by APT. Of special interest was the surface of anhydrous and hydrated tricalcium silicate. The results show, that a nanoscale characterization of tricalcium silicate with APT is possible by carefully controlling the various measurement parameters. Furthermore, our results indicate, that the conditions during focused ion beam sample preparation, especially the high vacuum and energy input, are potentially harmful to calcium-silicate-hydrate. Future developments in cryo sample preparation will greatly enhance the applicability of APT on cement and its hydration products.